Kedudukan dan Efektivitas Justice Collaborator di dalam Hukum Acara Pidana - Sirait, Adi Syahputra (IAIN Padangsidimpuan, 2019)
This article aims to analyze and explain the position of justice collaborator in criminal procedural law and the effectiveness of justice collaborator in proof, as an analysis instrument this research uses a case study of a narcotics-specific criminal decision in the Supreme Court where narcotics is an extraordinary crime committed in an organized manner by a drug syndicate narcotics, this research uses a social legal research approach using juridical type, the research data is obtained from an analysis of the decision of the Supreme Court of the Republic of Indonesia Number: 920K / Pid.Sus / 2013 which is then analyzed using the effectiveness theory. The Supreme Court Judge determines the defendant as a justice collaborator based on the Supreme Court circular number 4 of 2011 regarding the treatment of whistleblowers and witnesses of collaborating actors (justice collaborator). The results of this study are that the supreme court judge considered the defendant's petition as a justice collaborator who could reveal the illicit trafficking network of international channels and also reveal the main perpetrators of the narcotics distribution.